Chemoprophylaxis in addition to mechanical prophylaxis after total knee arthroplasty surgery does not reduce the incidence of venous thromboembolism - Loh, Jing Loong Moses (Thromb J, 2019)
BACKGROUND: Venous thromboembolism (VTE) of the lower limbs is an important complication post total knee arthroplasty (TKA). Current guidelines recommend routine chemical prophylaxis to all patients undergoing this procedure but this is rarely done in Asia as it is believed that Asians have a lower risk of VTE. However, recent evidence suggests otherwise. AIMS: We evaluated the incidence of DVT after TKA in a multi-ethnic Asian population with and without pharmacological prophylaxis, as well as the management and outcome of patients with post-operative DVTs. METHODS: We conducted a retrospective study of consecutive patients who underwent TKA in our hospital from 1st January 2004 to 30th December 2014. All patients were on mechanical thromboprophylaxis via calf pumps after TKA with a postoperative day 3 to 5 doppler ultrasound (DUS) of bilateral lower limbs. 2258 (80.7%) patients did not receive additional chemoprophylaxis, while 540 (19.3%) received chemoprophylaxis on top of mechanical thromboprophylaxis. All patients who received chemoprophylaxis were administered the drug until they were ambulating, with a median administration duration of 6 days. Patients were followed up for a period of 3 months for recurrence of DVTs and 24 months for postoperative outcome scores. RESULTS: Two thousand nine hundred seventy-eight patients had DUS of the lower limbs with 134 diagnosed with DVT giving an incidence of 4.5%. Six of these patients had concurrent PEs. There were 26 (19.4%) proximal DVTs and 108 (80.6%) distal DVTs. After 3 months of follow up, no additional VTE occurred. None of the DVTs or PEs progressed. All DVTs with accompanying PE were proximal. 102 out of 2200 patients (4.6%) without chemoprophylaxis developed DVT as compared to 32 out of 540 patients (5.9%) with chemoprophylaxis, which was not statistically significant (p = 0.13). 19 (0.8%) proximal and 83 (3.8%) distal DVT developed in the patient group without chemoprophylaxis while 4 (0.7%) proximal and 28 (5.2%) distal DVT developed in the patient group with (p = 0.62). Comparison of the incidence of PEs between the two groups, revealed a similar incidence with 5 out of 2200 patients (0.2%) without chemoprophylaxis developing PE as compared to 1 out of 540 patients (0.2%) with chemoprophylaxis (p = 0.87). In addition, patients with chemoprophylaxis showed an association with higher post-operative outcome scores such as post op 6 months SF36 (PCS), post op 12 months SF36 (PCS), post op 12 months SF36 (MCS), post op 24 months SF36 (MCS) and post op 24 months WOMAC. CONCLUSION: In one of the largest Asian studies specifically investigating the incidence of DVT after TKA, we found that the incidence is low at 4.5%. This is in contrast to recent studies that showed higher post-operative VTE rates similar to Western populations. In addition, patients who were administered chemoprophylaxis did not have a statistically significant difference in incidence of VTE although it did show a correlation with higher post-operative outcome scores which may indicate better function. This was seen in functional outcome scores such as post op 6 months SF36 (PCS), post op 12 months SF36 (PCS), post op 12 months SF36 (MCS), post op 24 months SF36 (MCS) and post op 24 months WOMAC.